Factors contributing to preterm birth in patients presenting at tertiary care hospitals in Punjab - Fariha Aslam Bajwa,; Nayyer Sultana,; Ameelia Sadaqat,; Abida Riaz,; Mirza Zeeshan Sikandar, (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the various causes and factors leading to preterm birth in women presenting at tertiary care hospitals. Method: The cross-sectional, prospective study was conducted from June 19, 2021, to January 19, 2022, at the Central Park Teaching Hospital, Lahore, Pakistan, in collaboration with other tertiary care teaching hospitals in Lahore, and comprised pregnant women aged 15-45 years with preterm birth. Demographic and obstetric data was collected. Depending on the factors contributing to preterm birth, the subjects were categorised as spontaneous labour group A, preterm prelabour rupture of membrane group B, and iatrogenic preterm birth group C. Data was analysed using SPSS 25. Results: Of the 1,300 recorded births, 200(15.38%) were preterm. Group A had 86(43%) women with mean age 28.55+4.68 years, group B had 43(21,5%) women with mean age 27.14+3.25+43 years, and group C had 71(35.5%) women with mean age 28.28+3.74 years (p>0.05). There was significant difference among the groups with respect to body mass index (p=0.001) and parity (p=0.021). Vaginal and urinary tract infections were significantly higher in group A compared to the other groups (p<0.05). In group C, pre-eclampsia was the main reason for preterm birth 45(63.38%). Conclusion: Medically indicated preterm birth rate was found to be high, and pre-eclampsia was noted as the main cause in iatrogenic preterm birth. Key Words: Preterm, Labour, Reproductive age, PPROM, Pre-eclampsia, Obstetrical complications.